THE EFFECT OF RECRUITMENT AND JOB PLACEMENT ON WORK ACHIEVEMENT AT PT. BANK TABUNGAN NEGARA (PESERO) TBK KCP SIBOLGA - Yenni Sofiana Tambunan; Nelly Azwarni Sinaga; Sinta Veronika Hutabarat (SEAN Institute, 2023)
This study entitled